Guided Discovery Learning: Suatu Pendekatan Konstruktivis untuk Penguatan Berpikir Kritis Siswa pada Materi Keanekaragaman Hayati - Devi Supriani; Aser Yalindua; Caroline Manuahe (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Critical thinking skills are an important competency in learning biology, especially in biodiversity materials that require analysis, reasoning, and decision-making. This study aims to determine the influence of the Guided Discovery Learning learning model on the critical thinking ability of grade X students at SMA Negeri 2 Tondano. The method used was a quasi-experimental study with a pretest-posttest control group design. The sample consisted of two classes, namely the control class that was taught using the conventional model and the experimental class that received treatment with the Guided Discovery Learning model. Data were collected through pretest and posttest written tests, and analyzed using normality, homogeneity, and t-test. The results showed that there was a significant difference between the learning outcomes of students in the experimental class and the control class. The average posttest score of the experimental class was 81 higher than the control class of 63.5. In addition, the Tcal value of 4.65 is greater than the Ttable of 2.02 at a significance level of 0.05, which shows that the Guided Discovery Learning model has a positive influence on improving students' critical thinking skills. This result is also strengthened by a decrease in standard deviation which shows an equal distribution of understanding between students. This research contributes to the development of active learning strategies in biology education and suggests the application of this model to improve higher-level thinking skills. This model is also relevant applied to other topics in order to strengthen discovery-based learning and collaboration.